MYD88 L265P mutation in cutaneous involvement by Waldenström macroglobulinemia. (5th May 2017) - Alegría‐Landa, Victoria; Prieto‐Torres, Lucía; Santonja, Carlos; Córdoba, Raul; Manso, Rebeca; Requena, Luis; Rodríguez‐Pinilla, Socorro M.
Abstract : Cutaneous manifestations of Waldenström macroglobulinemia (WM) may occur because of several mechanisms, the least common being direct skin infiltration by neoplastic cells. We report a case of patient that after 4‐year history of indolent WM developed skin infiltration by lymphoplasmacytoid cells in the form of a small, mildly indurated plaque on the anterior chest. MYD88 L265P mutation was detected both in the previous bone marrow biopsy and in the cutaneous lesion. We review the impact of this new genetic tool in the diagnosis and treatment of lymphoplasmacytic proliferations.